Boko Haram in Retrospect - Azumah, John Alembillah (Islam and Christian-Muslim relations, 2015)
This article looks at the development of the Nigerian Islamic militant group Boko Haram from an historical perspective and attempts to locate Boko Haram within an historical pattern of dissent and factionalism in Northern Nigerian Islam. It argues that the nineteenth-century jihadist legacy of Uthman dan Fodio, and its rejection of things non-Islamic, accusations of bidʿa and muwālāt and the invocation of takfīr, continues to appeal to the present-day generation of Muslims. Abubakar Mahmud Gumi, who viewed himself as a reformer in the tradition of dan Fodio, and his Wahhabi-inspired anti-Sufi views, and the activism of the Izala movement, which is an outgrowth of Gumi's religious and ideological views, have perpetuated the separatist tradition. From limited reliable data, the article goes on to construct the rise of Boko Haram (itself an outgrowth of the Izala movement) and its ideology from within the ranks of the Salafi-Wahhabi trends in Northern Nigeria, arguing that Boko Haram, with its militancy against things non-Islamic, is firmly rooted and best explained within the broader Northern Nigerian context of Islamic factionalism and absolutism fostered by a romanticized jihadist legacy and disillusionment arising from failed experiments with Salafi-Wahhabi idealism.